Phytoplankton community structure as a bioindicator of water quality in Lake Ranau, Lumbok Seminung District, West Lampung Regency, Lampung Province - Syahfitri, Amanda Trya; Kartini, Nidya; Yulianto, Herman (Acta Aquatica: Aquatic Sciences Journal, 2025)
The presence of phytoplankton greatly affects aquatic life because it plays an important role for aquatic biota. The purpose of this study was to identify the structure of the phytoplankton community, determine the condition of the waters and analyze the relationship between the structure of the phytoplankton community and the physical and chemical factors of the waters of Lake Ranau, Lumbok Seminung District, West Lampung. This study was conducted in November 2023 - January 2024. The determination of the research station used the purposive sampling method. Phytoplankton samples were taken using a 60 micron plankton net. Analysis of the effect of physical and chemical parameters of water on phytoplankton abundance was analyzed using PCA using statistical software. The results showed that the phytoplankton found consisted of 5 classes, namely Bacillariophyceae, Cyanophyceae, Chlorophyceae, Euglenophyceae, and Zgynematophyceae. The saprobic coefficient value of phytoplankton ranged from 0.2 - 0.7. This shows that the condition of the waters in Lake Ranau, Lumbok Seminung Regency is in a state of mild to moderate pollution. Environmental parameters that are positively correlated with phytoplankton abundance are DO, brightness, current velocity, and N/P ratio. Environmental parameters that are negatively correlated are temperature and parameters that do not affect phytoplankton abundance are H2S and pH.  Keywords: Lake Ranau; Phytoplankton; Saprobic